Krukovine Suppresses KRAS-Mutated Lung Cancer Cell Growth and Proliferation by Inhibiting the RAF-ERK Pathway and Inactivating AKT Pathway - Lai, Huanling; Wang, Yuwei; Duan, Fugang; Li, Ying; Jiang, Zebo; Luo, Lianxiang; Liu, Liang; Leung, Elaine L. H.; Yao, Xiaojun (Frontiers in Pharmacology, 2018)
Oncogenic activation of the KRAS gene via point mutations occurs in 20% to 30% of patients with non-small cell lung cancer (NSCLC). The RAS-RAF-ERK and RAS-PI3K-AKT pathways are the major hyper-activated downstream pathways in RAS mutation, which promotes the unlimited life cycle of cancer cells and their metastasis in humans. However, the success of targeted therapy is restricted by many factors. Herein, we show a new pharmacological KRAS signaling inhibitor named krukovine, which is a small molecular bisbenzylisoquinoline alkaloid isolated from the bark of Abuta grandifolia (Mart.) Sandw. (Menispermaceae). This alkaloid targets the KRAS downstream signaling pathways in different NSCLC cell lines, such as H460 and A549, which are established by KRAS mutations. In the present study, we initially investigated the anti-cancer activities of krukovine in KRAS-mutated NSCLC cell lines. Results indicated that krukovine can inhibit the growth and dose-dependently inhibit the colony formation capacity of H460 and A549. This cytotoxic effect is associated with the induction of cell apoptosis and G1 arrest in those cell lines. Krukovine treatment also suppressed the C-RAF, AKT, and ERK phosphorylation in H460 and A549. This finding suggests that krukovine represses the growth and proliferation of KRAS-mutated cells by inactivating AKT and downregulating the RAF-ERK signaling pathway. This study provides detailed insights into the novel cytotoxic mechanism of an anti-cancer compound from an herbal plant and promotes the compound’s anti-cancer potential in NSCLC with KRAS mutation.